The Role of Product Innovation in Consumer Purchase Intention at Multi Mart Jaya Store in Hargomulyo Village - Dwi Septianingsih; Fitrianingsih; Natasya Anggieta Putri; Senia Oktaviani; Murcitaningrum (Indonesian Journal Economic Review (IJER), 2026)
This study examines the role of product innovation in increasing consumer purchase intention at Multi Mart Jaya Store in Hargomulyo Village. The novelty of this research lies in analyzing product innovation in connection with the use of technology as a supporting factor to enhance purchase intention in a village-scale retail business. The study aims to analyze consumer purchase intention, identify obstacles causing low product innovation, and explain the impact of product innovation on consumer purchase behavior. This field research uses a qualitative approach. Data were collected through observation, in-depth interviews, and documentation. Informants included employees of Multi Mart Jaya who understand the store’s operations and consumer behavior trends. Data analysis was conducted descriptively through data reduction, data presentation, and conclusion drawing. The findings indicate that product innovation plays a crucial role in attracting and maintaining consumer purchase intention. However, limited capital, insufficient information about market trends, and low technology utilization have hindered optimal product innovation. This results in limited product variety, infrequent updates, and suboptimal promotion, which reduce consumer purchase intention. From an Islamic economics perspective, product innovation contributes to achieving maslahah by providing better products and services for consumers. In conclusion, enhancing product innovation supported by effective technology use can be an important strategy to improve business competitiveness and increase consumer purchase intention.